2014
DOI: 10.1002/cne.23562
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of sensory structures in the developing epidermis in sepia officinalis and other coleoid cephalopods

Abstract: Embryonic cuttlefish can first respond to a variety of sensory stimuli during early development in the egg capsule. To examine the neural basis of this ability, we investigated the emergence of sensory structures within the developing epidermis. We show that the skin facing the outer environment (not the skin lining the mantle cavity, for example) is derived from embryonic domains expressing the Sepia officinalis ortholog of pax3/7, a gene involved in epidermis specification in vertebrates. On the head, they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…We identified ciliated peripheral sensory neurons in the skin of hatchling O. bimaculoides using α-and β-tubulin antibodies. These cells were similar in morphology and position (Sundermann-Meister, 1978;Sundermann, 1983;Mackie, 2008;Buresi et al, 2014) to cells described as mechanoreceptors in both squid and cuttlefish (Budelmann and Bleckmann, 1988;Bleckmann et al, 1991). It is not yet known whether these peripheral sensory neurons act as mechanoreceptors in the skin of O. bimaculoides.…”
Section: Discussionmentioning
confidence: 62%
“…We identified ciliated peripheral sensory neurons in the skin of hatchling O. bimaculoides using α-and β-tubulin antibodies. These cells were similar in morphology and position (Sundermann-Meister, 1978;Sundermann, 1983;Mackie, 2008;Buresi et al, 2014) to cells described as mechanoreceptors in both squid and cuttlefish (Budelmann and Bleckmann, 1988;Bleckmann et al, 1991). It is not yet known whether these peripheral sensory neurons act as mechanoreceptors in the skin of O. bimaculoides.…”
Section: Discussionmentioning
confidence: 62%
“…This study focused on three genes associated with early tissue speciation. Previous studies have identified many genes implicated in cephalopod limb morphogenesis; future experimentation would especially benefit from timepoint‐ and treatment‐specific profiles, with particular emphasis on genes associated with nervous precursor distribution and development of complex sensory and neurological structures (Baratte & Bonnaud, ; Bassaglia et al, ; Buresi, Baratte, Da Silva, & Bonnaud, ; Buresi, Canali, Bonnaud, & Baratte, ; Buresi, Croll, Tiozzo, Bonnaud, & Baratte, ; Focareta, Sesso, & Cole, ; Zhang & Tublitz, ), as well as muscle (Bassaglia et al, ; Fossati et al, ; Navet et al, ; Zullo et al, ) and endothelium (Focareta & Cole, ). Additional genes of interest should be garnered from the available studies in models across taxa (Fei et al, ; Godwin et al, ; Kawakami et al, ; Uygur & Lee, ; Wischin et al, ); ideally strategies utilizing transcriptomic or single‐cell RNA sequencing could be compared on both amputated and regenerated limb tips to provide greater clarity on intraindividual variation in expression based on injury‐naïve and regenerating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…(d) In situ hybridization against Sof‐elav1 shows some of the nervous structures of the skin: Lateral lines along the arms and left olfactory organ (white arrow). Panel adapted with permission from Buresi, Croll, Tiozzo, Bonnaud, and Baratte (). CNS, central nervous system; Ey, eye; PNS, peripheral nervous system; Sh, shell; y, yolk.…”
Section: Methodsmentioning
confidence: 99%
“…The embryonic development of S. officinalis is arbitrarily subdivided into 30 stages based on major morphological changes (Lemaire, 1970). Organogenesis and neurogenesis start at around stage 12 and quickly form the nervous system with all of its components (Figure 1c) including the sensory organs and sensory cells (Baratte & Bonnaud, 2009;Buresi et al, 2014;Darmaillacq, Lesimple, & Dickel, 2008;Imarazene, Andouche, Bassaglia, Lopez, & Bonnaud-Ponticelli, 2017;Shigeno, Kidokoro, Tsuchiya, Segawa, & Yamamoto, 2001a;Shigeno, Tsuchiya, & Segawa, 2001b;Yamamoto, Shimazaki, & Shigeno, 2003), the integrative centers (Aroua, Andouche, Martin, Baratte, & Bonnaud, 2011;Buresi et al, 2014), and the connection of motor fibers to their target organs (Baratte & Bonnaud, 2009) early during organogenesis (Romagny, Darmaillacq, Guibe, Bellanger, & Dickel, 2012) soon after the differentiation of the associated sensory neurons ( Figure 1d). As we aimed to describe the distribution of HAergic neurons, this early sensory system development, in addition to the cephalopod's direct development life history, makes late-stage embryos (stages 27-30) a convenient model for sensory system and CNS observations.…”
Section: Embryos Of S Officinalis Develop Inside Eggs Laid In Intertmentioning
confidence: 99%
See 1 more Smart Citation